Embracing the endemic phase - Msctils goes hybrid - Asiah, Kassim (Centre for Modern Languages, 2022)
August 2022 – These couple of years have witnessed teaching and learning evolve in unexpected ways, with all the banes and boons tagging along as the consequence of the COVID19 affecting every nook and cranny of our lives. Master of Science in Technology-Integrated Language Studies (MScTILS) has also been in that boat sailing through the course passing all the hurdles that the pandemic has caused but that’s the way the cookies crumble.